Icodec insulin - revolution in diabetes type 2 insulin therapy - Dobrzyński, Michał; Czarnota, Jakub; Skubel, Tomasz; Drozd, Małgorzata; Dudek, Iga; Rybak, Natalia (Journal of Education, Health and Sport, 2022)
Introduction: Basal glucose control in diabetes type 2 is commonly maintained by a single, once-daily administration of insulin through subcutaneous injection. Insulin icodec, a novel ultralong-acting lipidated analog validates the concept of a once-weekly basal injection that is less burdensome, yet equally safe and efficacious as conventional once-daily treatment 1. Aim: The aim of the study is to introduce once-weekly injected insulin therapy and compare it with conventional basal insulin therapy in diabetes type 2 patients. Results: The results from phase II trials suggest that switching from an existing basal insulin to icodec, with or without a loading dose, provides effective glycemic control with comparable risk of hypoglycemia.In one of the studies TIR improved from baseline (mean: A 57.0%; B 55.2%; C 51.0%; IGlar U100 55.3%) through weeks 15 and 16 (estimated mean: A 76.6%; B 83.0%; C 80.9%; IGlar U100, 75.9%). No unexpected side effects were observed. It was reassuring that not a single episode of severe hypoglycemia (level 3) was reported for any treatment group throughout the trial duration and that the time spent below range (<3.9 mmol/L [<54 mg/dL]) during weeks 15 and 16 was well below the 4% target recommended by the International Consensus on Time in Range across all treatment groups 2. Conclusion: In conclusion,insulin icodec, a new acylated basal insulin analog, has been developed with optimized modifications to provide a long half-life suitable for weekly insulin dosing. In a patient population with type 2 diabetes receiving daily basal insulin therapy, switching to once-weekly icodec resulted in effective glycemic control without a transient elevation of fasting glucose levels during the switch and without increasing the risk of clinically relevant hypoglycemia compared with IGlar U100 2. Key words: Icodec, insulin, diabetes type 2